Muhammad Abduh dan Usaha Pembaharuan Pendidikan Islam di Mesir - Ratu Suntiah; Desi Rosulina; Mugeni Muhammad; Ayub Suganda; Nur Sab’rina Fathimah (Moral : Jurnal kajian Pendidikan Islam, 2025)
Muhammad Abduh was a reformer of the Islamic world in the 19th century who was famous for his efforts to raise the spirit and glory of Muslims. One of his focuses was on the renewal of the Islamic education system. In this article, we will review his biography, fundamental works, history of political struggle, ideas of renewal, methods in the renewal of Islamic education, portraits of his thoughts, and his influence on Islamic education, especially in Indonesia. Muhammad Abduh emphasized the importance of religious education that is balanced with general knowledge, as well as teaching methods that do not only rely on memorization but also on deep understanding. His thoughts developed in the aspects of religion, education, and socio-political society. His influence and relevance in the context of Indonesian Islamic education are prominent especially through organizations such as Muhammadiyah which were inspired by his thoughts. Through his works and ideas, Muhammad Abduh left a significant mark on the renewal of Islamic education.